Monitoring Eosinophilic Esophagitis Disease Activity With Blood Eosinophil Progenitor Levels. Issue 4 (April 2020) - Henderson, Anna; Magier, Adam; Schwartz, Justin T.; Martin, Lisa J.; Collins, Margaret H.; Putnam, Philip E.; Mukkada, Vincent A.; Abonia, J. Pablo; Rothenberg, Marc E.; Fulkerson, Patricia C.
ABSTRACT: Objectives: A minimally invasive biomarker to monitor disease activity is one of the greatest unmet clinical needs of the pediatric eosinophilic esophagitis (EoE) population. We aimed to determine whether circulating eosinophil progenitors (EoPs) could be used as a biomarker to identify pediatric patients with active EoE. Methods: In a prospective observational study, peripheral blood samples, symptom history, and laboratory data were collected from pediatric patients undergoing endoscopy for evaluation of EoE on dietary therapy at Cincinnati Children's Hospital. Peripheral blood EoP level was determined by flow cytometry. Results: Thirty-four children with active (n = 16) and inactive (n = 18) EoE were included in the analysis. EoP levels in the peripheral blood were 3-fold higher in patients with active EoE than inactive EoE ( P  < 0.0025). Blood absolute eosinophil count did not distinguish between active and inactive EoE ( P  = 0.16). A cut-off EoP level ≥17 accurately detected active disease in 79% of patients with 94.4% specificity and 62.5% sensitivity (area under the curve 0.81; P  < 0.0024 ). Antihistamine use lowered the threshold EoP level to detect active EoE. Conclusions: This study suggests that blood EoP levels may be used as a biomarker to detect active EoE disease in patients undergoing food trials and potentially reduce the need for repeated endoscopies. Larger prospective studies are needed to investigate the effects of antihistamines and swallowed steroids on EoP mobilization into the peripheral blood and longitudinal studies to assess the performance of the assay in individual patients over time. Abstract : Supplemental Digital Content is available in the text